2023
DOI: 10.5324/nje.v31i1-2.5606
|View full text |Cite
|
Sign up to set email alerts
|

The impact of longitudinal surveillance of individuals with cerebral palsy in Norway; a 20-year quality registry and follow-up program perspective

Sandra Julsen Hollung,
Reidun Jahnsen,
Gunvor Lilleholt Klevberg
et al.

Abstract: The Norwegian Quality and Surveillance Registry for Cerebral Palsy (NorCP) has systematically collecteddata on individuals with cerebral palsy (CP) and been a driver of knowledge dissemination for over 20 years.NorCP data have increased the competence of health professionals in both the municipal and specialisthealthcare services through publication of multiple scientific articles ranging from risk factors for CP tolifelong interventions, quality improvement projects, and training services. This has led to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 6 National hip surveillance programmes have been implemented in many countries to detect hip displacement earlier and to enable timely intervention. 7 - 12 Several studies have reported a significant decrease in the incidence of hip dislocation in regions where a hip surveillance programme has been introduced. 6 , 11 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 National hip surveillance programmes have been implemented in many countries to detect hip displacement earlier and to enable timely intervention. 7 - 12 Several studies have reported a significant decrease in the incidence of hip dislocation in regions where a hip surveillance programme has been introduced. 6 , 11 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…6 National hip surveillance programmes have been implemented in many countries to detect hip displacement earlier and to enable timely intervention. [7][8][9][10][11][12] Several studies have reported a significant decrease in the incidence of hip dislocation in regions where a hip surveillance programme has been introduced. 6,11,13 Currently, radiological hip analysis in surveillance programmes, such as the Cerebral Palsy Integrated Pathway Scotland (CPIPS), is performed manually by experts.…”
Section: Introductionmentioning
confidence: 99%